Analisis Penerimaan Penggunaan Aplikasi Mobile PeduliLindungi dengan Menggunakan UTAUT - Muhammad Burhanuddin Fawwaz; Sudewantoro Nur Muhammad; Hukama’ Nur R; Novanda Nurhandini Putri; Khansa Renata (Universitas Mercu Buana Yogyakarta, 2023)
During the COVID-19 pandemic, it greatly af ected various sectors of life for all countries in the world, including Indonesia. With this in mind, the government has developed an m-health mobile application as a solution in reducing the spread of COVID-19, namely mobile-based PeduliLindung. The public is now required to use the PeduliLindung mobile application every time they visit public facilities. This research was conducted with the aim of analyzing what factors can have an influence on the acceptance of the use of the PeduliLindung mobile application by the public. The research method was carried out by observation and distributing questionnaires to respondents. After that, an analysis was carried out using the UTAUT (Unified Theory of Acceptance and Use of Technology) model and data processing using the Structural Equation Model Partial Least Square (SEMPLS) with the help of SmartPLS 3.0 software. In this study, the results showed that 4 variables namely Performance Expectancy (PE), Ef ort Expectancy (EE), Social Influence (SI) and Facilitating Condition (FC) had a significant positive effect on Behavioral Intention to Use (BIUS) and overall the four variables only able to explain the influence on Behavioral Intention to Use by 47.1%.